CAR-exosomes derived from immune cells: an emerging nanoscale vanguard in overcoming tumor immunotherapy hurdles - Zhao, Xiaoyan; Zhao, Bin; Sun, Yan; Liu, Aiguo (Frontiers in Immunology, 2025)
Chimeric Antigen Receptor (CAR)-engineered cell therapies excel against hematologic malignancies, however, their efficacy in solid tumors is hampered by toxicity, poor tumor infiltration, immunosuppressive microenvironments, limited persistence, and expansion difficulties. Recently, exosomes derived from CAR-immune cells (CAR-Exosomes) have emerged rapidly as an innovative therapeutic platform. CAR-Exosomes, utilizing nanoscale communication pathways, inherit their parental cells’ tumor-targeting capabilities while offering distinct advantage. These advantages encompass low immunogenicity, enhanced tissue penetration, and versatile drug-loading capacity, presenting a promising approach to circumvent the limitations of traditional cell therapies. This review systematically summarizes the core challenges for CAR-T, CAR-NK, and CAR-M cell therapies and emphasizes recent advancements in CAR-Exosomes, including their molecular characteristics, targeted recognition mechanisms, tumor-killing pathways, biosafety, and engineering strategies. Furthermore, it also discusses the key challenges and strategies in the clinical translation of CAR-Exosomes. In conclusion, integrating nanomedicine with cell therapy, CAR-Exosomes hold significant promise as a next-generation platform aiming for high efficacy, safety, and broad clinical applicability in cancer immunotherapy.